Establishment of PHA Registry in Amnatcharoen Province - เชื้อลี, เสถียร (Disease Control Journal, 2010)
This study was designed for action research. The objective was to implement a PHA Registry in one pilot province, Amnatcharoen, in the Northeastern region of Thailand. It was conducted during May - December 2006 with the collaboration of researchers and health care providers working in PHA clinic, from hospitals in Amnat Charoen province. The study showed the PHA Registry systems, PHA Card, PHA Register and Patient book were very important in PHA care system. The PHA Registry system could be used as a comprehensive data source both for the update of the situation and the follow up of PHAs, for the detection for CD4 and Viral load and was very useful for treatment plans, screening for opportunity infections in PHAs. Many processes from PHA registry system could be used to verify data report and and improvement of clinical services in study areas. Nevertheless, a comprehensive reporting system needs to be established in order to have better data set and expand this project to cover other 7 provinces.